2011
DOI: 10.1523/jneurosci.2520-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Spine Dynamics Regulate the Long-Term Stability of Synaptic Plasticity

Abstract: Long-term synaptic plasticity requires postsynaptic influx of Ca 2ϩ and is accompanied by changes in dendritic spine size. Unless Ca 2ϩ influx mechanisms and spine volume scale proportionally, changes in spine size will modify spine Ca 2ϩ concentrations during subsequent synaptic activation. We show that the relationship between Ca 2ϩ influx and spine volume is a fundamental determinant of synaptic stability. If Ca 2ϩ influx is undercompensated for increases in spine size, then strong synapses are stabilized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 102 publications
(163 reference statements)
6
72
0
Order By: Relevance
“…Interestingly, the spine volume grows substantially as the synapse undergoes potentiation [42]. At first glance this suggests that the spine readies itself for potential further strengthening, but it has been suggested that actually the increase in spine volume reduces the calcium transients, limiting further potentiation, and therefore giving rise to soft-bound plasticity [43], [44].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the spine volume grows substantially as the synapse undergoes potentiation [42]. At first glance this suggests that the spine readies itself for potential further strengthening, but it has been suggested that actually the increase in spine volume reduces the calcium transients, limiting further potentiation, and therefore giving rise to soft-bound plasticity [43], [44].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, spine geometry can provide a local control of pCa, such that different synapses will indeed experience different pCa for the same barrage of synaptic input. Changes in spine geometry can act as a modulating factor to synaptic learning, with increasing spine size following LTP acting to stabilize synaptic weights by decreasing pCa at already potentiated synapses (O'Donnell, Nolan, & van Rossum, 2011 …”
Section: Implications For Synaptic Learningmentioning
confidence: 99%
“…87 Synaptic strength is proposed to be determined, in part, by postsynaptic influx of Ca 2þ , leading to changes in dendritic spine size, 88 and, if these changes are sustained, this can result in long-term synaptic plasticity. 89 "Weak" synapses, such as those found in "conditional multireceptive" brain regions (see Chapter 28), can undergo a much greater degree of increase than synapses that are more stable, such as those seen in primary sensory and motor networks. 90 …”
Section: Neurotropic Factorsmentioning
confidence: 99%